PERAN DINAS PENDIDIKAN KOTA PEKANBARU DALAM PENYELENGGARAAN PENDIDIKAN INKLUSIF TAHUN 2017 - Sari, Petty Indria Mayang; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Inclusive education is education that combines special needs students with normal students in a regular school to provide opportunities for all students who have physical, emotional, mental and social abnormalities in obtaining quality education in accordance with their needs and abilities. This is stated in the Minister of National Education Regulation No. 70 of 2009 concerning Inclusive Education for Students Who Have Abnormalities and Special Intelligence and / or Talent Potential. The researchers want to see the Role of Pekanbaru Education Office in the Implementation of 2017 Inclusive Education. This study aims (1) to find out the Role of Pekanbaru City Education Office in Implementing Inclusive Education 2017 (2) to find out the barriers to the role of Pekanbaru City Education Agency in Organizing Inclusive Education in 2017. The main research locations were conducted at the Pekanbaru City Education Agency. With the implementation of inclusive education researchers took two inclusive schools as appointed by the government, namely Pekanbaru 71 Elementary School and Bintang Cendekia Integrated Islamic Primary School Pekanbaru. The technique of collecting data is done by interviews and documentation. While the data analysis technique is done by qualitative descriptive analysis. Research Results The Role of Pekanbaru City Education Office in Implementing Inclusive Education in 2017 that the role of the Pekanbaru City Education Office in implementing inclusive education has not run optimally, which can be seen from planning inclusive education policies and programs, financial management for inclusive education, and training and development of personnel for inclusive education. The inhibiting factors in the implementation of inclusive education in the city of Pekanbaru include internal factors, namely the lack of a budget for inclusive education, lack of human resources and lack of facilities and infrastructure while external factors, namely public perceptions of inclusive education, lack of training related to inclusive education and lack of data collection inclusive school children with special needs. Keywords: Role, Pekanbaru City Education Agency, Inclusive Education